Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1101/2020.03.10.986695
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Weakest link dynamics predict apparent antibiotic interactions in a model cross-feeding community

Abstract: 13With the growing global threat of antimicrobial resistance, novel strategies are required for 14 combatting resistant pathogens. Combination therapy, wherein multiple drugs are used to treat an 15 infection, has proven highly successful in the treatment of cancer and HIV. However, this 16 practice has proven challenging for the treatment of bacterial infections due to difficulties in 17 selecting the correct combinations and dosages. An additional challenge in infection treatment is 18 the polymicrobial natu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…Next, several experimental evolution studies involving bacterial mutualisms have found that while some populations evolve a more efficient division of labour and elevated growth rates, other replicate populations experience unexplained collapse, leading to extinction of both interacting species 34,35 . Finally, a recent study exploring the adaptability of metabolically co-dependent bacterial populations in the presence of antibiotics showed that codependency between two species results in a limitation of their adaptation ability by the least adaptable, "weakest link" strain 36 . Thus, once a species is more adapted to the environment than its partner, it can not further increase in fitness until it's cooperator evolves to a similar fitness.…”
Section: Introductionmentioning
confidence: 99%
“…Next, several experimental evolution studies involving bacterial mutualisms have found that while some populations evolve a more efficient division of labour and elevated growth rates, other replicate populations experience unexplained collapse, leading to extinction of both interacting species 34,35 . Finally, a recent study exploring the adaptability of metabolically co-dependent bacterial populations in the presence of antibiotics showed that codependency between two species results in a limitation of their adaptation ability by the least adaptable, "weakest link" strain 36 . Thus, once a species is more adapted to the environment than its partner, it can not further increase in fitness until it's cooperator evolves to a similar fitness.…”
Section: Introductionmentioning
confidence: 99%